Development of advanced microbial communities for enhancing waste hydrolysis processes: insights from the application of molecular biology tools - Wilson, Laura Paige, author; De Long, Susan K., advisor; Sharvelle, Sybil, committee member; Bareither, Christopher, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2016)
Anaerobic digestion (AD) is an environmentally attractive technology for conversion of various solid wastes to energy. However, despite numerous benefits, AD applications to OFMSW remain limited in North America due to economic barriers with existing technologies. Suboptimal conditions in anaerobic digesters (e.g., presence of common inhibitors ammonia and salinity) limit waste hydrolysis in AD and lead to unstable performance and process failures compromising economic viability. To guide development of microbial management strategies to avoid process upsets and failures due to inhibitors, hydrolysis rates were determined in batch, single-stage digesters seeded with unacclimated or acclimated inocula under a range of ammonia and salinity concentrations for two model feedstocks (food waste and manure). Using unacclimated inocula, hydrolysis was found to be severely inhibited for elevated ammonia (decrease of nearly 4-fold relative to baseline) and salinity (decrease of up to 10-fold relative to baseline). However, for inocula acclimated over 2 to 4 months, statistically significant inhibition was not detectable except in the case of food waste subjected to elevated ammonia concentrations (p-value = 0.01). Inhibitors and feedstock were found to have a major influence on bacterial community structure. Next, a more detailed analysis of the acclimation process revealed that microbial communities under stressed conditions (elevated ammonia) adapt more slowly (weeks) to feedstock changes (from wastewater sludge to manure or filter paper) than under non-stressed conditions (days). Molecular tools were utilized to separate temporal effects on hydrolyzers from temporal effects on methanogens. Bacterial and archaeal sequencing results identified multiple organisms (e.g., Clostridiales vadinBB60, Ruminococcaceae, Marinilabiaceae, Methanobacterium, and Thermoplasmatales Incertae Sedis) that were selected for in microbial communities in stressed reactors under perturbed conditions (feedstock changes). Collectively, results from these studies suggested that weeks of acclimation are required to build up sufficient quantities of desired hydrolyzing microbes; thus, hydrolysis processes operated in batch mode should be inoculated with each new batch, and desired microorganisms should be maintained in the system via properly developed inoculation strategies. To identify improved methods of maintaining such communities in multi-stage reactor systems, reactor performance under elevated ammonia and salinity was compared for leach bed reactors (LBRs) seeded with unacclimated inoculum and different ratios of acclimated inoculum (0-60% by mass) at start-up. Additionally, the effect of seeding methods was examined by identifying the optimal ratio of fresh waste to previously digested waste in multi-stage systems incorporating leachate recycle during long-term operation. Results demonstrated that high quantities of inoculum (~60%) increase waste hydrolysis and are beneficial at start-up or when inhibitors are increasing. After start-up (~112 days) with high inoculum quantities, leachate recirculation leads to accumulation of inhibitor-tolerant hydrolyzing bacteria in leachate. During long-term operation, low inoculum quantities (~10%) effectively increase waste hydrolysis relative to without solids-derived inoculum. Additionally, molecular analyses indicated that combining digested solids with leachate-based inoculum doubles quantities of Bacteria contacting waste over a batch and supplies additional desirable phylotypes Bacteriodes and Clostridia. To provide detailed insight into microbial community activity during degradation, metatranscriptomic analyses were conducted on reactors fed food waste and manure under low ammonia, and several common active (e.g., Methanomicrobia, Methanosaeta concilii, and Clostridia) and unique active (e.g., Enterobacteriaceae, Clostridium thermocellum, and Clostridium celluloyticum) phylotypes between the reactors were identified. Functional classification of the active microbial communities generally revealed several similarities between the reactors despite the differences in feedstock. However, similarities or differences in transcript abundance for specific gene categories (e.g. one-carbon metabolism or fermentation) might indicate some potentially useful biomarkers for monitoring process health. Additionally, data from this experiment expanded the gene sequence database for assay development, which is particularly key for improving current functional gene-targeted assays to more accurately characterize microbial communities. Overall, results from this study have provided operational guidance for establishing and maintaining desired microbial communities as inocula to enhance waste hydrolysis for a variety of feedstocks.